PERCEPTION OF EASIENES IN USING FINTECH IN MSMEs - Bambang Sugiharto; Sri Mulyati; Aprillia Verra Puspita (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
This study aims to determine perceptions of the ease of use of fintech in MSMEs financing. The research method used is quantitative using primary data sources obtained through questionnaires distributed and filled out by respondents. The sampling technique used in this study was purposive sampling. The population in this study is MSMEs in Subang district. The results of the study indicate that there is a relationship between fintech and MSMEs financing, where MSME actors have increased sales due to fintech, fintech makes financing easy.